Understanding art education : engaging reflexively with practice - Addison, Nicholas, 1954- (Teaching school subjects 11-19 series., 2010)
A practical guide that puts art and design into perspective and shows teachers and student-teachers how to make the subject accessible and interesting to their pupils.